2022
DOI: 10.1186/s13052-022-01344-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the risk factors and clinical features of Mycoplasma pneumoniae pneumonia with embolism in children: a retrospective study

Abstract: Background Mycoplasmapneumoniae pneumonia (MPP) is a prevalent disease in community-acquired pneumonia among children. However, in addition to respiratory manifestations, it may also develop extra-pulmonary complications. Embolism is one of the uncommon extra-respiratory manifestations prone to severe sequelae and even death. This study aims to analyze the clinical features of MPP with embolism in children, and explore the associated risk factors of embolism in MPP patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Liu et al 4 reported that D-dimer >11.1 mg/L was useful for the early diagnosis of thrombus formation in pediatric MPP patients. Han et al’s 5 study found that D-dimer (closest to CTA/MRA) >3.55 mg/L was an independent risk factor for thrombotic complications in MPP children. Our study showed that D-dimer was a significant predictor of PT in SMPP patients, with an optimal cutoff value of 3.98 µg/mL, which was in agreement with the results of Han et al…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Liu et al 4 reported that D-dimer >11.1 mg/L was useful for the early diagnosis of thrombus formation in pediatric MPP patients. Han et al’s 5 study found that D-dimer (closest to CTA/MRA) >3.55 mg/L was an independent risk factor for thrombotic complications in MPP children. Our study showed that D-dimer was a significant predictor of PT in SMPP patients, with an optimal cutoff value of 3.98 µg/mL, which was in agreement with the results of Han et al…”
Section: Discussionmentioning
confidence: 98%
“…1,2 Although traditionally regarded as a self-limiting disease, it has recently garnered increased attention due to its association with serious complications, particularly vascular thrombotic diseases. 3,4 Pulmonary thrombosis (PT) is the most frequent thrombotic complication of MPP in children, 4,5 and domestic literature reports that Mycoplasma pneumoniae (MP) infection is one of the main risk factors for PT in this population. 6 Without timely diagnosis and treatment, PT ranks as the third leading cause of MPP-related mortality.…”
mentioning
confidence: 99%
“…Therefore, it's of vital signi cance to nd risk factors which indicate severe extra-pulmonary complication like cerebral infarction based on clinical manifestations, biochemical examinations and chest radiography. A retrospective casecontrol analysis [17] performed on 48 children with MP pneumonia found that pulmonary consolidation (⩾2/3 lobe), and pleural effusion were independent risk factors for embolism in children with MPP. In our literature review, 19/35 (54%) patients were found to have consolidation and 12/35 (34%) patients have pleural uid.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a hypercoagulable state combined with impaired endothelial anticoagulant function would facilitate subsequent embolism and lead to cerebral artery occlusion. MP infection can promote the body to produce auto-antibodies such as anticardiolipin antibodies (ACA), β2-glycoprotein antibodies or lupus anticoagulant antibodies, and then form immune complexes, resulting in the injury of respiratory tract and other organs outside the lungs [17]. Therefore, vasculitis is another mechanism causing cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Severe mycoplasma pneumonia with pulmonary consolidation was the most strongly associated risk factor for thrombosis. Among those cases reported from the embolism group, most cases are extracted from pulmonary embolism, whereas ventricle or cerebral embolism occurs rarely [ 17 ].…”
Section: Discussionmentioning
confidence: 99%